Liquid filmification from menisci. (22nd October 2015) - Spruijt, Evan; Le Guludec, Erwan; Lix, Clément; Wagner, Marc; Quéré, David
Abstract: A wetting liquid brought in contact with a solid covered by microtextures invades the network of textures and fills it, creating a liquid film whose thickness is fixed by the texture height. However, this process of filmification can be opposed by the presence of surrounding menisci, residing for instance in corners at the edges of the film. We discuss the nature to be given to the texture to overcome the negative Laplace pressure associated with menisci. We also describe how the dynamics of filmification is impacted by the design of the texture, focussing on micropillars, lines and grooves, and how it can be optimized for some texture density. We conclude by discussing the distribution of textures generating a constant velocity of filmification instead of the slowing-down classically observed in impregnation processes.